2019
DOI: 10.1016/j.ijwd.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Skin lightening practices, beliefs, and self-reported adverse effects among female health science students in Borama, Somaliland: A cross-sectional survey

Abstract: BackgroundSkin-lightening (SL) products are common, especially in Africa. Adverse effects from these products represent a public health concern. Use of these products in Somaliland is unknown.ObjectiveThis study aimed to determine the prevalence of use of SL products among female health science students, beliefs about these products and practices, and adverse effects experienced.MethodsThis was a cross-sectional survey of a convenience sample of female health science students at Amoud University in Borama, Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…9,10 In studies of female students in Ghana and Somaliland, more skin-lightening product users agreed that a lighter complexion gives a woman more confidence and increases the number of job opportunities and her chances of getting married. 9,15 These students were also influenced by relatives and advertisements on television. We had similar findings, and the majority of women in this study reported that they engaged in this practice to increase their attractiveness (60.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 In studies of female students in Ghana and Somaliland, more skin-lightening product users agreed that a lighter complexion gives a woman more confidence and increases the number of job opportunities and her chances of getting married. 9,15 These students were also influenced by relatives and advertisements on television. We had similar findings, and the majority of women in this study reported that they engaged in this practice to increase their attractiveness (60.9%).…”
Section: Discussionmentioning
confidence: 99%
“…13 , 14 A recent study of female health science students in Somaliland found that 25.6% of subjects reported past or present use of skin-lightening products and 52.2% admitted to current use. 15 In Ghana, 1 study found that mercurial soaps and hydroquinone were more commonly used than steroids and the most common cutaneous complications were exogenous ochronosis and colloid milia. 16 In another study, squamous cell carcinoma developed in a patient after prolonged skin lightening with hydroquinone.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 75% of women in Nigeria ( Dadzie and Petit, 2009 , Dlova et al, 2015 ), 60% in Senegal ( Blay, 2011 ), 50% in Mali ( Baxter, 2000 ), and 30% in Ghana are estimated to use bleaching creams regularly, with similar rates in other African countries ( Lartey et al, 2017 , Mckinley, 2001 ).Throughout the continent, both men and women are frequently targeted with marketing campaigns showing public figures who bleach their skin ( Owusu-Agyei et al, 2020 ). Consequently, individuals claim that lighter skin makes them attractive and increases their career opportunities ( Dlova et al, 2015 , Yusuf et al, 2019 ).…”
Section: Regionsmentioning
confidence: 99%
“…1 ; Dlova et al, 2015 , Lartey et al, 2017 ). Similarly, in regions of East Africa, 52% of patients use SL products for pigmentary disorders, 38.7% prefer a lighter skin color, and 9.7% report both reasons ( Yusuf et al, 2019 ).
Fig.
…”
Section: Regionsmentioning
confidence: 99%
See 1 more Smart Citation